Technology use and learning characteristics of students in higher education: Do generational differences exist? - Lai, Kwok-Wing; Hong, Kian Sam (British Educational Research Association, 2015)
As digital technologies form an inextricable part of young people’s everyday lives, some commentators claim that the current generation of learners think and learn differently from their predecessors. This study investigated the validity of this claim by surveying 799 undergraduate and 81 postgraduate students at a large research-intensive university in New Zealand to document their use of digital technologies on university and social activities and comparing three age groups of students (under 20, 20–30 and over 30) to see whether there were any differences in their learning characteristics. The findings of the study showed that while students spent a large amount of time on digital technologies, the range of digital technologies they used was rather limited. There were also no practical generational differences in the technology use pattern and learning characteristics found in this study. The results of this study suggest that generation is not a determining factor in students’ use of digital technologies for learning nor has generation had a radical impact on learning characteristics of higher education students.